2009
DOI: 10.1242/jcs.038208
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Staufen 1 is recruited to stress granules and impairs their assembly

Abstract: SummaryMammalian Staufen 1 is recruited to stress granules and impairs their assembly Journal of Cell Science 564 is considered to be a global mRNA-binding factor, as it was shown to bind to different RNA motifs, including G-quartets, the β-actin zip code, the Myc 3ЈUTR; the FMR1 3ЈUTR, the HIV transactivating response region and the so-called Staufen-binding motif (Rackham and Brown, 2004;Dugré-Brisson et al., 2005; Kim, Y. K. et al., 2005). Recently, at least 7% of cellular mRNAs were shown to be present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 62 publications
(104 reference statements)
11
146
0
5
Order By: Relevance
“…As reported previously, we found that TIA1 and TIAR have a nuclear localization under resting conditions, and that, shortly after stress induction, numerous small aggregates containing TIA1, TIAR and eIF3 begin to form in the cytoplasm (supplementary material Fig. S1A,B) (reviewed by Anderson and Kedersha, 2006;Anderson and Kedersha, 2008;Thomas et al, 2009). Soon afterwards, these particles collapsed into larger granules (supplementary material Fig.…”
Section: Retrograde Transport Mediated By Dhc1 and Bicd1 Is Required supporting
confidence: 73%
See 2 more Smart Citations
“…As reported previously, we found that TIA1 and TIAR have a nuclear localization under resting conditions, and that, shortly after stress induction, numerous small aggregates containing TIA1, TIAR and eIF3 begin to form in the cytoplasm (supplementary material Fig. S1A,B) (reviewed by Anderson and Kedersha, 2006;Anderson and Kedersha, 2008;Thomas et al, 2009). Soon afterwards, these particles collapsed into larger granules (supplementary material Fig.…”
Section: Retrograde Transport Mediated By Dhc1 and Bicd1 Is Required supporting
confidence: 73%
“…PBs are present in resting cells and they are further induced upon stress. SGs grow in close contact with PBs, suggesting that an active flow of mRNAs and proteins occurs between the two types of foci (reviewed by Anderson and Kedersha, 2008;Ohn et al, 2008;Mollet et al, 2008;Thomas et al, 2009). Both PBs and SGs are in equilibrium with translating polysomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress granules form during the translational silencing triggered by cellular stress, and XRN1 is recruited to stress granules under specific conditions (Thomas et al, 2009;Thomas et al, 2011). To investigate whether the XRN1 puncta induced concomitantly with the translational silencing triggered by NMDA are stress granules, we assessed the presence of the eukaryotic translation factor 3g (eIF3g, also known as EIF3B), a widely accepted stress granule marker.…”
Section: Xrn1 Forms Synaptic Bodies That Are Different From Processinmentioning
confidence: 99%
“…In flies, 3′ UTR-bound Staufen is required for proper localization and translational control of bicoid and prospero mRNAs during oogenesis 4,5 . In mammals, Stau1 has been implicated in mRNA transport to neuronal dendrites 6 , regulation of translation via physical interaction with the ribosome 7 , a form of translation-dependent mRNA degradation known as Staufen-mediated decay (SMD) [8][9][10][11] , regulation of stress-granule homeostasis 12 , alternative splicing, nuclear export and translation of a gene containing 3′-UTR CUG-repeat expansions 13 . Although Stau1 is not essential for mammalian development, neurons lacking Stau1 have dendritic spinemorphogenesis defects in vitro, and knockout mice have locomotor-activity deficits 14 .…”
mentioning
confidence: 99%